The Communication in Mechatronic Systems - Kallay, Fedor; Peniak, Peter (Communications - Scientific letters of the University of Zilina, 2007)
The paper deals with mechatronic systems and communication among mechatronic modules. This article proposes possible solution of usage open CAL protocol above CAN bus, which is independent from any manufacturers and can be widely accepted themselves. The main attention is paid to open CAN/CAL protocols including the viewpoint of their implementation, essential functions and potential integration within the vehicle control system. The required communication functions, communication models, communication objects (PDO, SDO) and applied profiles are being described in the CAL protocol. As an example a double bus CAN system is shown as a typical CAN/CAL solution for mechatronic systems in automotive industry.